Impact of Broken Homes on Education of Children: A Sociological Perspective - Mayowa, Ilori Oladapo (International Journal of Criminology and Sociology, 2021)
Broken Homes, until very recently is very alien to the African family structure/setting. But it is discovered that the trend of Broken Homes is growing in the world all over and Africa is not left behind in this trend. One can deduce the growing trend of Broken Homes in Africa to the incursion of modernization and industrialization into the African family setup. The traditional African family is much knitted together with a lot of love bound. But with modernization and civilisation are fast becoming the order of the day in all sectors of daily life, family is not left behinIn Nigeria for instance, the existence of Broken Homes is unknown, and when they existed, they are ignored as exceptional cases. In Africa, no one is happy to be identified as being raised in a Broken Home. In order words, the pride of an average African Child is to be brought up in a family where the man and his dear wife are living together, loving each other and each one of them performing his/her social responsibility and obligation towards the raising of the children and the survival of the family at large. This research looked at how broken home has affected education of children in society today and proffered solutions on how the scourge could be contained in our society. The research is mainly literature and conceptual. Literature in this study was sourced mainly from secondary data like journals, books, and the views of other scholars in this field.